Factors Influencing Adoption of Accrual Based International Public Sector Accounting Standards and Impacts on Quality of Financial Reporting in the UAE Public Sector - Elharon, Esam Omar Saleh (2023)
Financial reporting in the public sector is important for the UAE as it ensures transparency and accountability in the use of public funds. This transparency is essential for maintaining public trust and confidence in government institutions, promoting good governance practices, and facilitating decision-making to achieve long-term development goals. The adoption of International Public Sector Accounting Standards (IPSAS) has been instrumental in enhancing the transparency and consistency of financial reporting, ultimately leading to improved decision-making and accountability. This study aims to examine the impacts of different independent variables of IPSAS adoption on the quality of financial reporting in Dubai, while also considering the mediating effect of IPSAS adoption. The proposed conceptual framework incorporates seven independent variables: top management support, knowledge and experience, training, implementation cost, external pressure, availability of expertise, and technology, in addition to IPSAS adoption as a mediator. Furthermore, both Agency theory and Institutional theory support the proposed conceptual framework. The study’s population consists of accountants and auditors, both internal and external, engaged in periodic bookkeeping and financial statement reporting in accordance with IPSAS standards within Dubai’s public organisations. There are approximately 43 public entities in Dubai, resulting in a potential respondent pool of 430 possible respondents. Data collection was conducted in 2022, resulting in a final dataset comprising 232 responses. The analysis of the study’s hypotheses revealed that six hypotheses were not supported. These include two direct relationships for quality of financial reporting, two direct relationships for IPSAS adoption, and two mediating relationships. Notably, three of the rejected hypotheses pertain to the cost of implementation. For decision-makers in Dubai and beyond, this study contributes by highlighting the significance of external pressure in driving IPSAS adoption and, consequently, improving financial reporting quality. Interestingly, the study reveals that the cost of implementation is not a significant factor affecting the quality of financial reporting. The findings also contribute to academic literature by providing empirical evidence from an emerging country, examining IPSAS adoption as a mediator, and proposing a refined model for understanding the relationship between IPSAS adoption and the quality of financial reporting. Future studies are encouraged to replicate this model in different countries to facilitate generalization and comparison. Additionally, future studies could delve into the reasons behind the rejection of the cost of implementation by experts interviews.